Students’ Concept Mastery with the Web Inquiry Environment - Dewi, Pramita Sylvia; Komikesari, Happy; Mahfud, Ashari; Kusumah, Raden Gamal Tamrin (Indonesian Journal of Science and Mathematics Education, 2022)
Technology has a vital role in the field of education. After the COVID-19 pandemic, the learning system has become more flexible. To keep making arrangements according to the development of the situation in the classroom and to avoid student passivity, an online platform is needed that involves students in conducting investigations. The study aimed to determine the student’s ability to understand the concepts in the discussion of Archimedes' Law.The participants involved consisted of 53 grade 7 junior high school students. The method used was descriptive quantitative to investigate students' inquiry abilities and determine their understanding of concepts. The research on concept mastery shows a significant difference in using web inquiry environment after the treatment. Therefore, the web inquiry environment is essential to improve students' concept mastery.Implementing the web inquiry environment is recommended to consider topics with experiments to ensure that all inquiry processes can be carried out efficiently.